The prevalence and socio-demographic correlates of depressive symptoms among Cypriot university students: a cross-sectional descriptive co-relational study - Sokratous, Sokratis; Merkouris, Anastasios; Middleton, Nicos; Karanikola, Maria (My University, 2014)
Background: Previous findings in the literature suggest that the occurrence of depressive symptoms among university students is associated with specific socio-demographic characteristics. No related research studies have been conducted among university students in Cyprus. The current study aims to add more evidence to the literature by estimating the prevalence of clinical depressive symptoms and their association with individual, parental, academic and health-related behavior characteristics. Methods: A descriptive cross sectional study with internal comparison was performed. The occurrence of depressive symptoms was assessed by the Center for Epidemiology Studies - Depression Scale (CES-D). Clinical depressive symptoms were reported as CES-D values ≥ 20. The socio-demographic and other characteristics of the participants were assessed using a questionnaire specifically designed for the present study. Both questionnaires were completed anonymously and voluntarily by 1,500 students (29.9% males and 70.1% females, response rate 85%). Results: The prevalence of clinical depressive symptoms [CES-D score ≥ 20] was 27.9%. Among other, strong positive associations with clinical depressive symptoms were observed with a) positive personal and family history of depression (OR 2.85, 95% CI: 1.77 – 4.60), b) self -assessed poor physical and mental health (OR 11.30, 95% CI: 7.05 – 18.08). Moreover, students with learning disabilities, as well as those who were dissatisfied with the major under study, the quality of the educational system, the living arrangement, their social life and the available university facilities (OR 2.73, 95% CI: 2.00 – 3.72) were more likely to report clinical depressive symptoms. Conclusions: The results of the present study highlight specific individual, parental, academic and health-related behavior characteristics of the students associated with the presence of depressive symptoms. Thus, targeted interventions considering the socio-demographic profile of vulnerable students for early recognition and manifestation of mental health disturbances may be designed. Moreover, the relatively high prevalence of clinical symptoms of depression within this particular cultural context may warrant further investigation in longitudinal studies.
Keywords: Depression; Psychological distress; Psychiatric symptoms; Young adults; Cyprus; Students; Center for Epidemiology Studies- Depression Scale (CES-D); Parental characteristics; Health related behaviors; Clinical symptoms